Super-Resolution Correlative Light and Electron Microscopy (SR-CLEM) Reveals Novel Ultrastructural Insights Into Dendritic Cell Podosomes - Joosten, Ben; Willemse, Marieke; Fransen, Jack; Cambi, Alessandra; van den Dries, Koen (Frontiers in Immunology, 2018)
Podosomes are multimolecular cytoskeletal structures that coordinate the migration of tissue-resident dendritic cells (DCs). They consist of a protrusive actin-rich core and an adhesive integrin-rich ring that contains adaptor proteins such as vinculin and zyxin. Individual podosomes are typically interconnected by a dense network of actin filaments giving rise to large podosome clusters. The actin density in podosome clusters complicates the analysis of podosomes by light microscopy alone. Here, we present an optimized procedure for performing super-resolution correlative light and electron microscopy (SR-CLEM) to study the organization of multiple proteins with respect to actin in podosome clusters at the ventral plasma membrane of DCs. We demonstrate that our procedure is suited to correlate at least three colors in super-resolution Airyscan microscopy with scanning electron microscopy (SEM). Using this procedure, we first reveal an intriguing complexity in the organization of ventral and radiating actin filaments in clusters formed by DCs which was not properly detected before by light microscopy alone. Next, we demonstrate a differential organization of vinculin and zyxin with respect to the actin filaments at podosomes. While vinculin mostly resides at sites where the actin filaments connect to the cell membrane, zyxin is primarily associated with filaments close to and on top of the core. Finally, we reveal a novel actin-based structure with SEM that connects closely associated podosome cores and which may be important for podosome topography sensing. Interestingly, these interpodosomal connections, in contrast to the radiating and ventral actin filaments appear to be insensitive to inhibition of actin polymerization suggesting that these pools of actin are not dynamically coupled. Together, our work demonstrates the power of correlating different imaging modalities for studying multimolecular cellular structures and could potentially be further exploited to study processes at the ventral plasma membrane of immune cells such as clathrin-mediated endocytosis or immune synapse formation.